Metabolism and biomass vertical distribution of zooplankton in the Bransfield Strait during the austral summer of 2000 - Yebra Mora, Lidia; Hernández-León, Santiago; Almeida, Carlos; Becognée, Pierrick (Polar Research, 2011)
The vertical distribution (0?550 m) of zooplankton biomass, and indices of\nrespiration (electron transfer system [ETS]) and structural growth (aminoacyltRNA\nsynthetases activity [AARS]), were studied in waters off the Antarctic\nPeninsula during the austral summer of 2000. The dominant species were the\ncopepod Metridia gerlachei and the euphausiid Euphausia superba. We observed\na vertical krill/copepod substitution in the water column. The zooplankton\nbiomass in the layer at a depth of 200?500 m was of the same magnitude as the\nbiomass in the layer at a depth of 0?200 m, indicating that biomass in the\nmesopelagic zone is an important fraction of the total zooplankton in Antarctic\nwaters. The metabolic rates of the zooplankton community were sustained\nby less than 0.5% of the primary production in the area, suggesting that\nmicroplankton or small copepods are the main food source. Neither food\navailability nor predation seemed to control mesozooplankton biomass. The\nwide time lag between the abundance peak of the dominant copepod (M.\ngerlachei) and the phytoplankton bloom is suggested to be the main explanation\nfor the low summer zooplankton biomass observed in these waters. 425 415 0,909 Q3 SCIE